RISC FACTORS IN BILIARY TRACT SURGERY (SOME REFLECTIONS ON 2000 PATIENTS HAVE BEEN TREATMENTED SURGICALLY) - İsmail KAYABALI,; Sezai YILMAZ,; Betül BOZKURT, (Turkish Journal of Gastroenterology, 2020)
-